Principles and practices of money and banking - Whittlesey, Charles R. (New York : Macmillan, 1954)
The book explains monetary and banking system as a developing organism within which, despite the continuous process of change, certain lasting principles and concepts were discernible.
Includes bibliographical references and index.
obn 22/01/2019
Loans
Keywords: Money; Banks and banking